The importance of education and role of educational institutions in climate change mitigation and achieving UN SDG 13 “Climate Action” - Priatna, Dolly; Khan, Shujaul Mulk (Indonesian Journal of Applied Environmental Studies, 2024)
Climate change is a long-term shift in weather patterns driven by natural and human activities, leading to global warming and extreme weather events. Education - both formal and informal, plays a crucial role in climate change mitigation by enhancing awareness, fostering critical thinking, and promoting sustainable practices. It equips individuals with the knowledge and skills necessary to understand the complexities of climate change and engage them in informed decision-making. Education also promotes innovation and solutions, supports policy and advocacy, builds resilience, and empowers vulnerable populations. Climate change mitigation strategies align with Sustainable Development Goal 13 (SDG 13) “Climate Action”, but they also present synergies and trade-offs with other SDGs. Large-scale implementation of technologies can positively impact economic growth and job creation, but environmental issues linked to mineral extraction can detract from other SDGs. Careful management is essential to balance these interactions and minimize trade-offs. Educational institutions play a crucial role in achieving Sustainable Development Goal 13 (SDG 13) by fostering knowledge, research, advocacy, and sustainable practices. They contribute to climate education and awareness through curriculum development, research and innovation, leadership and institutional action, policy advocacy, capacity building, community engagement, ethical and sustainable values education, and monitoring and reporting. Higher education institutions can integrate climate change education into curricula, equipping students with the necessary skills to address environmental challenges. They can also promote global citizenship and empower individuals to contribute to climate solutions. By incorporating multidisciplinary approaches, educational institutions can bridge gaps in climate education and promote innovative solutions to mitigate climate impacts.